EVALUATION OF THE SOFT SKILLS DEVELOPMENT PROGRAM FOR EDUCATORS AND EDUCATIONAL PERSONNEL AT THE ALGHIFARI FOUNDATION - Muslikhin, Muslikhin; Baihaqi, Mohammad Aqil; Haprilwanti, Nenden; Badrudin, Badrudin (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This article analyzes the impact of soft skills development on the performance of educators and educational staff at Yayasan Alghifari, using a quantitative approach through an ex post facto method and Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) analysis. The study aims to evaluate the effectiveness of existing soft skills training programs and their relationship with performance aspects such as communication, collaboration, adaptability, and problem-solving. The results show that several factors have a highly significant and significant impact on other variables. Stress management has a highly significant effect on adaptability (path coefficient = 0.523, p-value = 0.000), followed by the significant effect of adaptability on leadership (path coefficient = 0.412, p-value = 0.001). Moreover, effective communication is found to significantly enhance collaboration and teamwork (path coefficient = 0.689, p-value = 0.000), which, in turn, significantly contributes to problem-solving ability (path coefficient = 0.612, p-value = 0.000). Problem-solving also has a highly significant impact on innovation and creativity (path coefficient = 0.754, p-value = 0.000). Other factors with a significant impact include listening skills on collaboration and teamwork (path coefficient = 0.321, p-value = 0.002), and professional ethics and responsibility on innovation and creativity (path coefficient = 0.467, p-value = 0.000). However, the hypothesis testing the effect of time management on problem-solving ability did not show significant results (path coefficient = 0.089, p-value = 0.145). These findings offer new insights into the importance of factors such as stress management, effective communication, and problem-solving in enhancing innovation and creativity within organizations. The strength of this article lies in its significant findings, which provide a solid foundation for improving human resource development policies in the education sector, particularly in the development of relevant and applicable soft skills for educators and educational staff